Thyroid hemiagenesis is combined with a variety of thyroid disorders - Schneider, Christina; Dietlein, Markus; Faust, Michael; Drzezga, Alexander; Schmidt, Matthias (Nuklearmedizin - NuclearMedicine, 2019)
Aim Thyroid hemiagenesis (TH) is a rare congenital anomaly in which one thyroid lobe fails to develop. We describe our experience with at least 13 patients presenting with TH at our department.Methods We retrospectively analysed patients with TH, who had been referred primarily to our clinic between 2004 and 2010. In patients with TH, thyroid function parameters and thyroid autoantibodies were examined. 99mTc-pertechnetate thyroid scintigraphy and sonography were performed in all patients and confirmed the diagnosis of TH.Results We identified 13 patients (11 women, 2 men) with TH in our patient collective and calculated an estimated prevalence of TH of 0.08 %.We found TH to occur more frequently in the left lobe and also more frequently in females than in males. 9 patients presented with a total absence of one thyroid lobe and 4 patients presented with severe hypoplasia of one thyroid lobe with an isthmus appearing as a “hockey stick sign” on scintigraphic imaging. Associated thyroid diseases could be observed in the remaining lobe in all patients and included hyperthyroidism, hypothyroidism, nodular goiter, toxic goiter, hypofunctioning nodules, Graves’ disease and Hashimoto-thyroiditis. The most frequent thyroid disease in our patients with TH was nodular goiter. We did not find any association of TH with malignancy.Conclusion TH is mostly detected incidentally as the prevalence of TH is extraordinary low. The fact that all of our patients with TH were also affected by other forms of thyroid disease is reasonable since the patients were not referred to the diagnostic centre due to TH but rather due to the associated thyroid disease. Possibly there are different groups of TH: the symptomatic hypothyroid children, the lifelong euthyroid adults who are diagnosed incidentally through another thyroid disease and the patients with a molecular failure of proper thyroid development.
Keywords: Thyroid hemiagenesis; thyroid disorder; nodular goiter; hyperthyroidism; hypothyroidism